Phytochemical, antioxidant and antimicrobial activity of Livistona chinensis (Jacq.) R.Br. ex Mart. seeds - Tamanna Beniwal; Ritu Sharma
The seeds of Livistona chinensis (Jacq.) R.Br. ex Mart.(Family: Arecaceae) plant traditionally find application in the treatment of various diseases. Therefore, in the present study, phytochemical screening and biological profiling of Livistona chinensis seed extracts were conducted. The bioactive components were analysed using GC-MS and UHPLC-QTOF-MS and the fatty acid composition was determined using FAME analysis. GC-MS analysis results indicated the presence of oleic acid (35.71%) and palmitic acid (30.7%) as major components in the seed extract prepared in n-hexane. UHPLC-QTOF-MS analysis revealed the presence of 25 secondary metabolites, including isobutyric acid, acetoin, 9-oxononanoic acid, piperidine, umbellic acid, furaneol, and ketopantolactone in the methanolic extract of seeds. FAME analysis results suggested the presence of oleic acid (18.44%), lauric acid (11.66%), linoleic acid (11.30%), linolenic acid (10.20%), and palmitic acid (9.96%) in abundance. In biological profiling, Livistona chinensis seed extracts were subjected to in vitroantimicrobial, and antioxidant activity. The aqueous extract exclusively showed antimicrobial activity, and exhibited inhibition zone of 16.1 mm only against gram-negative bacteria (Klebsiella pneumonia). The methanolic extract demonstrated maximum antioxidant activity, at sample concentration of 200 (So(BL. These findings suggest that Livistona chinensis seeds might be a potential source of bioactive metabolites, antimicrobial agents, and antioxidant agents that may be utilised in pharmaceutical, cosmetics, and food industriess